Assessment of Knowledge about First Aid, Diagnosis and Prevention of Snake Bite among Medical Students: A Cross Sectional Study - Bhandari, Binus; Khadka, Dipendra; Shakya, Arbin (Journal of Nepalgunj Medical College, 2024)
Introduction: Snakebite is a global health problem and important medical emergency encountered in many parts of the world with considerable morbidity and mortality. Knowledge and awareness about snake bite directly impacts outcome.Aims: To assess the knowledge about first aid, diagnosis and prevention of snake bite among medical students.Methods: A cross sectional study was conducted among the MBBS students of Nepalgunj Medical College. Semi-structured questionnaires were used to assess the knowledge about first aid, diagnosis and prevention of snake bite among medical students of both non-clinical and clinical group.Results: Total students enrolled were 321. Among them 230 (71.7%) were male and 91 (28.3%) were female with male preponderance Majority of students belonged to clinical level 61.4% as compared to non-clinical 38.6%. Regarding first aid knowledge, majority of clinical students responds correctly as compared to non-clinical. Clinical diagnosis of snake on the basis of recognizing signs and symptoms, both clinical and non-clinical groups had satisfactory response. Similarly regarding preventive measures, results showed majority of the students from both the groups were aware about preventive measures against snake bite.Conclusion: Both clinical and non-clinical students have adequate knowledge regarding clinical diagnosis and preventive measures against snake bite but first aid knowledge was more among clinical students. Integrating snake bite topic from early non-clinical stage will positively reflect on the care for snakebite victims.